Degradation of a novel herbicide fluchloraminopyr in soil: Dissipation kinetics, degradation pathways, transformation products identification and ecotoxicity assessment - Wentao Zhou; Wenbo Zhang; Huiluan Han; Xiaohu Wu; Jun Xu; Fengshou Dong; Yongquan Zheng; Xiangwei Wu; Xinglu Pan (Environment International)
With the continuous application of new agricultural chemicals in agricultural systems, it is imperative to study the environmental fate and potential transformation products (TPs) of these chemicals to better assess their ecological and health risks, as well as guide scientific application. The dissipation of fluchloraminopyr was firstly evaluated under aerobic/anaerobic condition in four representative soils, with Dissipation Time 50 (DT50) values ranging from 0.107 to 4.76 days. Eight TPs generated by soil degradation were identified via Ultra-High Performance Liquid Chromatography coupled with Quadrupole Time-of-Flight Mass Spectrometry (UHPLC-QTOF/MS) and Density Functional Theory (DFT) calculations. The predominant transformation reactions of fluchloraminopyr in soil include oxidation, dechlorination, hydroxylation, and acetylation. The predictions from toxicological software indicated that the acute and chronic toxicity of TPs to aquatic organisms was significantly lower than that of fluchloraminopyr. Moreover, both M267 and M221 exhibited higher acute oral toxicity to terrestrial organisms compared to the parent compound. Consequently, these findings offer essential ecological risk evaluation data for the judicious application of fluchloraminopyr.